Pemilihan Umum Menurut Hukum Islam - Sodikin Sodikin (Universitas Islam Negeri Jakarta, 2015)
This article discuss the implementating general election in Islamic law, both the legislative elections, elections of regional heads and presidential elections. Indonesian elections in accordance with the mechanism of the western democracies, so that the election is the only way in choosing representatives and leaders. In the Islamic view of the elections is not the only way but one of the ways to choose a government or leader. Elections according to the Islamic view of the law may permissible, but must be in accordance with the implementation of sharia, not using a mechanical cause many western democracies not helpful.DOI: 10.15408/ajis.v15i1.2848